Stock assessment of Bombay duck Harpodon nehereus (Ham.) off Maharashtra coast - Kurian, Alexander; Kurup, K Narayana (Indian Journal of Fisheries, 2011)
The dol nets contribute the major share to the landing of Bombay duck Harpodon nehereus. Features of thedol net fishery, fishing area and seasonal distribution of the fishery are presented. Biological studies are chieflyconfined to food and feeding habits, analysis of maturity stages, sex ratio and length-weight relationship. Thelength at 50% maturity was observed as 230 mm. Different spawning cycles were noticed and fecundity evinceda linear increase with fish weight. The growth parameters and mortality estimates were made. Assuming tenninalexploitation rate as 0.78, the average catch was observed to be 52 213 tonnes. MSY estimated by Thompsonand BeUmodel was 54 631 tonnes and biomass MSY as 76 893 tonnes and hence it was assumed that the Bombayduck along the Maharashtra coast was optimally exploited.